EXPLORING THE USE OF FIGURATIVE LANGUAGE: AN ANALYSIS OF THE NOVEL “5 CENTIMETERS PER SECOND” WRITTEN BY MAKOTO SHINKAI - Rengga Mahendra; Edi Ardian; Samsul Amri (J-Shelves of Indragiri (JSI), 2026)
Figurative language is a crucial element of literary expression, enriching narratives by conveying complex emotions and imagery beyond literal meaning, thereby deepening reader engagement and thematic resonance. Despite extensive research on figurative language in literature, specific analyses focusing on its distribution and function within contemporary translated Japanese novels particularly the melancholic and poetic works of Makoto Shinkai, such as 5 Centimeters Per Second remain underexplored. This study aims to identify and analyze the types, frequency, and functions of figurative language specifically simile, metaphor, hyperbole, and verbal irony in the English translation of Shinkai’s novel, in order to understand its contribution to the narrative’s emotional and thematic impact. Employing a descriptive qualitative approach with purposive sampling, the researcher systematically identified and interpreted figurative expressions within the text. Key findings reveal that metaphor (42,2%) and simile (37,1%) dominate the figurative landscape, collectively constituting 79,3% of instances. These are used extensively to evoke vivid imagery and profound emotional depth (e.g., “Akari’s presence had been my only lifeline”). Hyperbole appears less frequently (20,3%), intensifying moments of emotional extremity, while verbal irony is entirely absent (0%), aligning with the novel’s earnest, introspective tone. The study concludes that Shinkai strategically prioritizes metaphor and simile to explore themes of distance, longing, and transience, utilizes hyperbole for dramatic emphasis, and eschews irony to maintain emotional sincerity. This pattern underscores how figurative language functions as a primary vehicle for the novel’s poignant storytelling.